the Effect of Website-Based Formative Assessment to Improve Students’ Conceptual Understanding in Dynamic Fluid Topic - Sasmita, Fauzia Dwi; Kusairi, Sentot; Khusaini, Khusaini (Universitas Negeri Padang, 2024)
Conceptual understanding is an important goal in learning because it is required to develop a deep understanding of how the concepts inter-relate with each other. However, students’ conceptual understanding, especially in dynamic fluid topics, are still relatively low. One of the reasons behind this issue is the limited time for teachers to provide direct feedback to each student. This research focused on analyzing the effect of website-based formative assessment (Fortion) to improve students’ conceptual understanding in dynamic fluid topics. This research is a quasi-experimental study with One Group Pretest-Posttest Design. The sample in this research were 66 students of 11th grade from Public School in Banjarmasin City. The instruments used in this research was learning achievement tests. Data analysis was carried out through the Wilcoxon test. This research showed that there was an effect of website-based formative assessment (Fortion) in order to improve students’ conceptual understanding in dynamic fluid topics. Thus, the exploration of website-based formative assessment on different topics needs to be held in future research so that Fortion can be more effectively used by students to enhance their conceptual understanding.